Neonatal and pediatric extracorporeal membrane oxygenation in developing Latin American countries - Javier Kattan; Álvaro González; Andrés Castillo; Luiz Fernando Caneo
Abstract Objective: To review the principles of neonatal-pediatric extracorporeal membrane oxygenation therapy, prognosis, and its establishment in limited resource-limited countries in Latino America. Sources: The PubMed database was explored from 1985 up to the present, selecting from highly-indexed and leading Latin American journals, and Extracorporeal Life Support Organization reports. Summary of the findings: Extracorporeal membrane oxygenation provides "time" for pulmonary and cardiac rest and for recovery. It is used in the neonatal-pediatric field as a rescue therapy for more than 1300 patients with respiratory failure and around 1000 patients with cardiac diseases per year. The best results in short- and long-term survival are among patients with isolated respiratory diseases, currently established as a standard therapy in referral centers for high-risk patients. The first neonatal/pediatric extracorporeal membrane oxygenation Program in Latin America was established in Chile in 2003, which was also the first program in Latin America to affiliate with the Extracorporeal Life Support Organization. New extracorporeal membrane oxygenation programs have been developed in recent years in referral centers in Argentina, Colombia, Brazil, Mexico, Perú, Costa Rica, and Chile, which are currently funding the Latin American Extracorporeal Life Support Organization chapter. Conclusions: The best results in short- and long-term survival are in patients with isolated respiratory diseases. Today extracorporeal membrane oxygenation therapy is a standard therapy in some Latin American referral centers. It is hoped that these new extracorporeal membrane oxygenation centers will have a positive impact on the survival of newborns and children with respiratory or cardiac failure, and that they will be available for an increasing number of patients from this region in the near future.